Gap Analysis CPOB 2018 Terhadap Rancangan Revisi CPOB 2024 Aneks 1 Pembuatan Produk Steril Aspek Peralatan, Sarana Penunjang, dan Personalia - Gracia Anastasya; Taofik Rusdiana; Ella Fazila (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The pharmaceutical industry operates under a strict regulatory framework to ensure that the products produced are safe, of high quality, and effective. These regulations are continuously updated to keep up with advancements in science, technological developments, and global demands for higher quality standards. The pharmaceutical industry also faces the challenge of global regulatory harmonization, such as standards set by WHO and PIC/S. These regulations are designed to ensure drug quality from development to distribution. Changes in Good Manufacturing Practices (GMP) regulations are crucial for improving pharmaceutical production quality in Indonesia. This study aims to conduct a gap analysis between the 2018 GMP and the draft 2024 GMP Annex 1, particularly in terms of equipment, supporting facilities, and personnel. The method used is a comparative analysis by comparing the provisions of the 2018 GMP with the draft 2024 GMP. The gap analysis results between the 2018 GMP and the draft 2024 GMP Annex 1 in terms of equipment, supporting facilities, personnel, and sterile product completion indicate significant changes in the adopted standards. The proposed 2024 GMP revision introduces substantial improvements in sterile product manufacturing standards. As part of efforts to enhance global competitiveness, the Indonesian pharmaceutical industry must continue to adapt to dynamic technological and regulatory changes. By implementing various strategies—including substantial investments in modern equipment, adjustments to supporting facilities, and capacity building for personnel—the Indonesian pharmaceutical industry can meet global standards while ensuring the availability of safe, high-quality, and effective sterile products for the public.